Concurrent hypereosinophilic syndrome and deep vein thrombosis after Pfizer‐BioNTech COVID‐19 vaccination: A case report. Issue 3 (2nd March 2023) - Yano, Shungo; Miyagami, Taiju; Furusaka, Takayuki; Kano, Nagamasa; Naito, Toshio
Abstract: Herein, we report a case of eosinophilia syndrome and deep vein thrombosis presenting concurrently after the administration of the BNT162b2 mRNA‐based coronavirus disease 2019 (COVID‐19) vaccine. It is extremely rare to have both hypereosinophilic syndrome and deep vein thrombosis simultaneously. Both are serious diseases and should be treated with caution. Abstract : We experienced a complicated case of eosinophilia syndrome and deep vein thrombosis after administration of BNT162b2 mRNA‐based coronavirus disease 2019 (COVID‐19) vaccine. It is extremely rare to have both hypereosinophilic syndrome and deep vein thrombosis simultaneously. Both are serious diseases and should be treated with caution.